Metabolomics approach for food safety authentication - Ahmad Fadzillah, Nurrulhidayah; Elgharbawy, Amal A.M.; Windarsih, Anjar; Rohman, Abdul (Academic Press, Elsevier, 2026)
The growing global halal market necessitates robust methods for food authentication and safety. This chapter examines metabolomics as a powerful tool for ensuring food integrity, particularly in the context of halal authentication. We detail how a comprehensive analysis of small-molecule metabolites, combined with advanced analytical platforms such as LC-MS, GC-MS, and nuclear magnetic resonance (NMR) spectroscopy, can detect subtle biochemical variations indicative of adulteration, geographical origin, and processing effects. The inherent data complexity is addressed through chemometrics, utilizing techniques such as principal component analysis (PCA) for exploratory analysis and partial least-squares discriminant analysis (PLS-DA) for precise classification and biomarker identification. Case studies demonstrate the efficacy of metabolomics in detecting non-halal components (e.g., pork adulteration in meat products) with high accuracy and sensitivity. While challenges in standardization and database development remain, future directions point toward portable biosensors, artificial intelligence integration, and multiomics approaches to enhance food traceability and consumer trust.